Revisiting the classics: Janet Chan and the legacy of 'Changing Police Culture'. (18th May 2016) - O'Neill, Megan
ABSTRACT: As a field of social science research, policing has been fortunate to have a number of influential academic researchers and a rich history of significant writing. This is something to be celebrated. Our Revisiting the Classics series aims to bring together leading commentators to review books that contribute to the core of police studies. There will always be debate about which books are the most significant and which authors have had the greatest influence on the discipline. We hope this initiative will encourage readers to rediscover the value of work done by previous generations. In this article, Megan O'Neill explores Janet Chan's text, Changing Police Culture, which brought about a significant diversification in police culture research.